Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3389/fcell.2021.654518
|View full text |Cite
|
Sign up to set email alerts
|

A Composite Lactide-Mineral 3D-Printed Scaffold for Bone Repair and Regeneration

Abstract: Orthopedic tumor resection, trauma, or degenerative disease surgeries can result in large bone defects and often require bone grafting. However, standard autologous bone grafting has been associated with donor site morbidity and/or limited quantity. As an alternate, allografts with or without metallic or polyether-etherketone have been used as grafting substitutes. However, these may have drawbacks as well, including stress shielding, pseudarthrosis, disease-transmission, and infection. There is therefore a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 79 publications
(100 reference statements)
0
11
0
Order By: Relevance
“…Therefore, local delivery of ZA would reduce the risk of experiencing side effects [57] , [72] . This can be achieved by using impregnated 3D-printed nanoporous scaffolds [73] . In vitro studies have shown that with a 3D-printer, it is possible to customize a model and insert it in a bone defect to allow bone marrow stem cells to infiltrate, adhere, proliferate, and form new bone [73] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, local delivery of ZA would reduce the risk of experiencing side effects [57] , [72] . This can be achieved by using impregnated 3D-printed nanoporous scaffolds [73] . In vitro studies have shown that with a 3D-printer, it is possible to customize a model and insert it in a bone defect to allow bone marrow stem cells to infiltrate, adhere, proliferate, and form new bone [73] .…”
Section: Discussionmentioning
confidence: 99%
“…This can be achieved by using impregnated 3D-printed nanoporous scaffolds [73] . In vitro studies have shown that with a 3D-printer, it is possible to customize a model and insert it in a bone defect to allow bone marrow stem cells to infiltrate, adhere, proliferate, and form new bone [73] . Such approach showed promising results where approximately 3 µM of ZA impregnated into nanoscaffolds or beads was enough to achieve the same therapeutic concentration locally as the systemic dose of 4 mg upon intravenous administration [70] , [71] .…”
Section: Discussionmentioning
confidence: 99%
“…It has been estimated that there will be about 28 million orthopedic surgery procedures worldwide by 2022, and a critical issue is the demand for bone substitutes will greatly increase, which is the second most transplanted tissue annually now [37] . Due to the drawbacks of immune response, donor site morbidity and shortage of supply, it seems that autografts and allograft will not fully cover the needs of bone transplantation [38,39] . Therefore, BTE, which aims to fabricate bioactive bone scaffold for substitutions of bone tissue, is showing a promising prospect in repairing bone defect.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to assisting bioceramic or metallic particles in preparing composite scaffolds, polymers have a promising future. 100 , 101 By means of 3D printing, Ce Zhu et al prepared PEEK/graphene composite scaffolds. The scaffolds were subsequently electrophoretically deposited (EPD) with drug-loaded bioactive coatings based on hydroxyapatite (HA).…”
Section: Application Of Different Types Of 3d Printed Biological Scaf...mentioning
confidence: 99%